Screening biotoxin aptamer and their application of optical aptasensor in food stuff: a review - Sun, Jiefang; Zhang, Meng; Gao, Qianlong; Shao, Bing (Frontiers in Chemistry, 2024)
Biotoxins are ranges of toxic substances produced by animals, plants and microorganisms, which could contaminate foods during their production, processing, transportation or storage, thus leading to foodborne illness, even food terrorism.Therefore, proposing simple, rapid and effective detection methods for ensuring food free from biotoxin contaminate show highly realistic demand. Aptamers are singlestranded oligonucleotide obtained from the systematic evolution of ligands by exponential enrichment (SELEX). They can specifically bind to wide ranges of targets with high affinity, thus have become attractive recognizing units in safety monitoring in food control and anti-terrorism. In this paper, we reviewed the technical points and difficulties of typical aptamer screening processes for biotoxin. For promoting understanding of food control in the food supply chain, the latest progresses in rapid optical detection of biotoxin based on aptamer was summarized. In the end, we outlined some challenges and perspects in this field. We hope this paper could stimulate wide interests in developing advanced sensing systems for ensuring food safety.